2012
DOI: 10.1111/j.1540-6210.2012.02565.x
|View full text |Cite
|
Sign up to set email alerts
|

New Executives from Inside or Outside? The Effect of Executive Replacement on Organizational Change

Abstract: This article investigates how executive succession influences the comprehensiveness of structural changes pursued by public organizations. Executive successions are important events for organizations that provide salient opportunities for introducing organizational change, yet little research has analyzed this relationship. The author argues that the less familiarity a new executive has with the organization and the field in which it works, the more likely it is that comprehensive organizational change will ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 29 publications
0
36
0
1
Order By: Relevance
“…The results of the present study suggest that one explanation of that finding may be that outside successors operate with a larger administration in the years after assuming their executive position and need time to settle in in their new position. In another study Villadsen (2012) shows that outside successors are likely to initiate larger structural changes than are inside successors in the period following their appointment. A by-product of more substantial structural changes may be the need for more coordination, which may constitute an additional explanation for the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the present study suggest that one explanation of that finding may be that outside successors operate with a larger administration in the years after assuming their executive position and need time to settle in in their new position. In another study Villadsen (2012) shows that outside successors are likely to initiate larger structural changes than are inside successors in the period following their appointment. A by-product of more substantial structural changes may be the need for more coordination, which may constitute an additional explanation for the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Putting new ideas into life is also likely to require a strong and supportive corporate centre that can link to other parts of the organization. This need is further amplified by external successors tending to engage in major changes requiring effective support functions (Villadsen 2012). …”
Section: Hypothesis 2: the Effect Of Executive Succession On Administmentioning
confidence: 99%
See 1 more Smart Citation
“…This insight has explained why organizations are more likely to adopt practices that were present at a new manager's previous place of employment (Kraatz and Moore, 2002). Along these lines it has also been found that managers with previous employment outside the field of a new organization are more likely to carry out more profound organizational changes (Villadsen, 2012). Similarly, we may expect managerial networking to be affected by experience in other sectors or other parts of the public sector.…”
Section: Personal Factorsmentioning
confidence: 91%
“…We build on this research by taking a longitudinal stance, and regard the influence of CEs on their organizations' propensity to hire MCS as likely to change as new experiences are made. Inspired by recent studies in public administration research, we do so by focusing on a specific aspect of CE characteristics: tenure (see, e.g., Esteve et al, ), which has been shown to be closely related to organizational change in public organizations (Villadsen, ) a typical reason for the use of consultants. Thus, in contrast to previous research that has focused on rather static characteristics such as public managers' gender (Meier, O'Toole, & Goerdel, ), our approach turns interest to variations over time (Damanpour & Schneider, ).…”
Section: Upper Echelon Theory and Hypothesis Developmentmentioning
confidence: 99%